O pensamento político de Gabriel González Videla e sua experiência brasileira – os anos de reformulação e praxis política – (1942-1948) - Astudillo, Claudio Andrés Pino (2019)
This research studies the relationship between the diplomatic experience of Gabriel González Videla in Brazil (1942-1944), the (re) formulation of his political thought and his anti-Communist behavior during his first years as President of the Republic of Chile (1946/1948) -1952). In order to accomplish that, we have investigated an important part of the public and private life of the character, who revealed significant data to understand how the politician, a Radical Party (PR) whose doctrine was characterized by adherence to the rationalist principles of extreme liberalism, ended being a staunch anticommunist in the name of defending the democratic regime at the dawn of the Cold War. Methodologically, we use content analysis as the main strategy for the construction of the corpus of our research, which is entirely is constituted by primary and secondary sources. It is important to warn the reader about the fact that the Memories of Gabriel, were an essential part of the documentation studied, which retain biases and opinions that are anachronistic to the events reported and witnessed by our character. The results obtained indicated that the Brazilian diplomatic experience had little influence on Gabriel's anticommunist thinking, but they also revealed the transcendental importance of Brazil in other aspects for the character.